"It is for Everything": Religiosocial Discourse Experiences of Methodist Youth. Issue 1 (2nd January 2020) - Rackley, Eric D.
Abstract: Informed by interpretive phenomenological analysis and sociocultural theory, this study examines the language experiences of seven Methodist youth. Analysis of 9 months of observations and 30 interviews yielded a set of experiences that represent the intimacy and complexity of youths' religious discourses. As an essential feature of this congregation, discourse helped create a safe religious learning environment, fostered positive social relationships, and helped youth develop personally. On occasion, youth also violated acceptable discourse boundaries, sparking tension and uncertainty. At the intersection of religion, language, and social contexts, this study raises questions about the relationship between words and (religio)social worlds.